5PSQ-032 Monitoring of indicator for the correct prevention of hospital infections and planning for improving interventions at a surgical hospital. (2nd March 2018) - Fantini, L; Polidori, C; Trombetta, L; Maio, L Di; Iovino, P; Melfi, MA; Luppi, M; Lucidi, C; Pede, S Di; Sassoli, V
Abstract : Background: Antibiotic preventive care in a surgical hospital is very important: the main cause of surgical infections is the endogenous bacteria flora of patients. For this reason, in 2009, a multidisciplinary team defined the new guideline (LG) providing: one single shot of cefazolina 2 g, replaced by clindamicyn 600 mg in allergic patients; and the administration of prophylaxis from 30 to 60 min before the incision. The team also identified indicators to monitor the correct prevention of hospital infections: comply with LG, timing respect, and use of hydroalcoholic solution for hand-washing, defined correctly by OMS between 10 to 20 litres for 1, 000 days of hospitalisation. Purpose: Indicators were monitored to verify the accuracy of prevention measures and on the basis of obtained results, a programme was possible for improving interventions. Material and methods: In order to verify LG adherence of prophylaxis, antibiotics prescription has been controlled in a sample of 189 medical records. Timing administration registered by the operating theatre programme had been verified and the consumption of hydroalcoholic solution for hand-washing has been controlled according to the pharmacy management programme for 2016. Results: Medical records indicate an adherence of nearly 100% to LG: in 189 medical records only two resulted in not complying with prophylaxis continuation up to patient discharge. Timing administration was respected only in 65% of cases: 5% received cefazolina after 60 min and the other 30% received it before 30 min. Gel consumption for handwashing was 23 litres gel/100 hospitalisation days. Conclusion: Adherence to prophylaxis has been achieved, therefore only periodic monitoring is to be continued. The use of hydroalcoholic solution for hand-washing is slightly higher than the OMS guideline and to make sure that hand-washing is carried out in the correct way, dedicated timers will be mounted on faucets. Timing administration, on the contrary, is still poor, so that is why there will be a meeting with anaesthesiologists in order to decide future strategy. No conflict of interest